2022
DOI: 10.1021/acs.iecr.2c02668
|View full text |Cite
|
Sign up to set email alerts
|

Phosphorus Removal from Dirty Farmyard Water by Activated Anaerobic-Digestion-Derived Biochar

Abstract: The management of anaerobic digestate is important to realize the value of the waste and enhance the whole system sustainability of anaerobic digestion. In this study, the phosphorus treatment of dirty irrigation water by biochar samples derived from digestate of anaerobic digestion were investigated. The biochars were further activated by steam activation with different duration time and KOH activation with different introducing ratios; the textural properties of biochars were optimized after activation from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 52 publications
(78 reference statements)
0
4
0
Order By: Relevance
“…Number of studies have been reported regarding the use of Mg/Ca-biochar to treat piggery digestive wastewater (He et al, 2022), river water (H. , acid extract of incinerated sewage sludge ash (Fang et al, 2020), municipal water (Mitrogiannis et al, 2017, lake water (Samaraweera et al, 2021a), dirty irrigation water (Zhang et al, 2022), and tap water (Han et al, 2022). Due to the co-existing contaminants (heavy metals, oxyanions, and dyes etc.)…”
Section: Treatment Of Phosphate In Real Wastewatermentioning
confidence: 99%
See 1 more Smart Citation
“…Number of studies have been reported regarding the use of Mg/Ca-biochar to treat piggery digestive wastewater (He et al, 2022), river water (H. , acid extract of incinerated sewage sludge ash (Fang et al, 2020), municipal water (Mitrogiannis et al, 2017, lake water (Samaraweera et al, 2021a), dirty irrigation water (Zhang et al, 2022), and tap water (Han et al, 2022). Due to the co-existing contaminants (heavy metals, oxyanions, and dyes etc.)…”
Section: Treatment Of Phosphate In Real Wastewatermentioning
confidence: 99%
“…The SSs (108 ton/y) contain Al 3+ , Ca 2+ , Mg 2+ , and Fe 3+ enhancing the surface complexation by the electrostatic interactions of PO4 3− ions and SS annually produced from steel manufacturing industries (Shin et al, 2023). Zhang et al (2022) used seawater as a cheap and efficient Ca/Mg source for the biochar modification. The resulting modified biochar exhibited a large phosphate uptake, 181 mg/g, and low production cost $0.41 per kg.…”
Section: Materials Optimizationmentioning
confidence: 99%
“…Carbonaceous materials like biochar have been employed as effective solid sorbents for soil amendment, phosphorus removal, and carbon capture. The biomass feedstock for producing the biochars can come from spruce [18], reeds [19], sheep manure [20], dairy cow slurry [21], date seed biochar [22], and sewage sludge [23]. Due to its sustainability and low-cost benefits for treating wastewater containing heavy metals, sludge biochar has recently attracted much attention [24].…”
Section: Introductionmentioning
confidence: 99%
“…However, biochar is typically not as effective at adsorption as activated carbon. 18,19 Therefore, the purpose of this work is to prepare activated carbon from the digestate of food waste using a chemical activation procedure using HNO 3 to enhance the adsorption capacity. To our knowledge, the preparation of activated carbon from the digestate of food waste and the HNO 3 treatment of the carbon-based material adsorbent for enhanced methylene blue (MB) removal from water have not been reported.…”
Section: Introductionmentioning
confidence: 99%